Disney after dark - Pearson, Ridley (Pearson, Ridley. Kingdom keepers, 2020)
Finn Whitman and four other teenagers are hired to be guides at Walt Disney World in Florida. The theme park uses a new DHI technology to transform the teens into hologram projections that guide the guests around. However, DHI--which means both Disney Host Interactive and Daylight Hologram Imaging--leads Finn and his friends into the Magic Kingdom after hours where they learn that the park is in danger. As they try to save Disney World, the five teens encounter a series of Disney villains and witches.